Identity Through Iteration: Secondary Imagemaking Practices as Expressions of Cultural Continuity, Change and Interpretation in the Rock Art of Southern Africa - Andrew Skinner (Genealogy, 2025)
This paper examines secondary rock art practices in southern Africa and how they served as mechanisms for expressing and negotiating identity through iterative engagement with existing artistic traditions. Often dismissed as mere ’graffiti’ or vandalism, these practices of modifying, adding to, or reinterpreting historic rock art represent sophisticated forms of engagement with inherited cultural landscapes. Through detailed analysis of mode, placement, and technique, this article demonstrates how secondary artists used existing imagery as both physical and symbolic resources, selectively mobilising earlier artforms to articulate their own positions within changing social worlds. With their technical choices encoding specific attitudes towards inherited traditions, secondary artists appear as one of many audiences—a range which includes contemporary researchers—engaging with these artistic traditions as subjects of common interest, their modifications creating material epistolaries that capture how different communities understood and positioned themselves relative to their own imaginations of the past. By reconceptualising these practices as meaningful interpretive acts rather than degradation, this paper contributes to broader discussions about how African identities have been articulated, contested, and preserved through active engagement with cultural heritage across time.